2019
DOI: 10.1111/cge.13516
|View full text |Cite
|
Sign up to set email alerts
|

Expanding the clinical spectrum associated with PACS2 mutations

Abstract: Whole exome sequencing (WES) has led to the understanding of the molecular events affecting neurodevelopment in an extremely diverse clinical context, including diseases with intellectual disability (ID) associated with variable central nervous system (CNS) malformations, and developmental and epileptic encephalopathies (DEEs). Recently, PACS2 mutations have been causally linked to a DEE with cerebellar dysgenesis and facial dysmorphism. All known patients presented with a recurrent de novo missense mutation, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
42
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(47 citation statements)
references
References 12 publications
(17 reference statements)
3
42
0
2
Order By: Relevance
“…The epileptic encephalopathy of neonatal‐onset, caused by sequence variants of the PACS2 gene, located on chromosome band 14q32.33 4,5 and referred to here as PACS2 syndrome, is worthy of special mention. PACS2 encodes a multifunctional sorting protein involved in nuclear gene expression and pathway traffic regulation, it is transcribed in brain tissue where it is enriched in glial cell–enriched white matter.…”
Section: Pacs2 Syndromementioning
confidence: 99%
See 3 more Smart Citations
“…The epileptic encephalopathy of neonatal‐onset, caused by sequence variants of the PACS2 gene, located on chromosome band 14q32.33 4,5 and referred to here as PACS2 syndrome, is worthy of special mention. PACS2 encodes a multifunctional sorting protein involved in nuclear gene expression and pathway traffic regulation, it is transcribed in brain tissue where it is enriched in glial cell–enriched white matter.…”
Section: Pacs2 Syndromementioning
confidence: 99%
“…Finally, the mutation may affect mTORC2/Akt role in neuronal migration and dendritic arborization, 5 and the mTOR complex is causally involved in various forms of genetic and structural epilepsies 34 . Olson et al 5 found the same de novo missense variant p.Glu209Lys in 14 patients, whereas Dentici et al 4 found missense variant p.Glu211Lys in another patient. PACS2 syndrome is a complex condition characterized by hypotonia, motor and intellectual delay, behavioral issues, dysmorphic face with hypertelorism, broad nasal sella and thin upper lip, minor distal limb abnormalities, cerebellar dysgenesis, and very early onset epilepsy.…”
Section: Pacs2 Syndromementioning
confidence: 99%
See 2 more Smart Citations
“…К настоящему времени в гене PACS2 описана еще одна нуклеотидная замена c.631G>A (p.Glu211Lys), возникшая de novo у пациента с эпилепсией с дебютом приступов в возрасте 3 дней, дискинезией мозжечка и лицевыми дизморфиями [7]. Первый адверсивный приступ возник на фоне респираторного дистресса и сопровождался потерей сознания.…”
Section: клинический случайunclassified